2014
DOI: 10.3109/02656736.2014.887793
|View full text |Cite
|
Sign up to set email alerts
|

Heat exposure enhances radiosensitivity by depressing DNA-PK kinase activity during double strand break repair

Abstract: It was suggested that NHEJ is the major process used to repair X-ray-induced DSBs and utilises DNA-PKcs activity, but homologous recombination repair provides additional secondary levels of DSB repair. The thermo-sensitisation in X-ray-irradiated cells depends on the inhibition of NHEJ repair through the depression of DNA-PKcs activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 41 publications
0
42
0
1
Order By: Relevance
“…It was later suggested that hyperthermia can act as a radio-sensitizer by interfering with the repair of DSBs as it may have an impact on c-NHEJ, alt-NHEJ and HR collectively [93]. Recent work showed that exposure to hyperthermia can restrict the activity of DNA-PKs in addition to reducing protein levels of KU70, KU80, BRCA1 and 53BP1 with the first two in greater extent [94]. Finally, given that various chemotherapeutic agents have the ability to trigger the induction of DSBs, inhibitors of DNA ligases and/or DNA-PKs appear to sensitize tumor cells to chemotherapeutic drugs thus providing alternative therapeutic strategies which potentially can be more effective [95,96].…”
Section: Non-homologous End Joining (Nhej)mentioning
confidence: 99%
“…It was later suggested that hyperthermia can act as a radio-sensitizer by interfering with the repair of DSBs as it may have an impact on c-NHEJ, alt-NHEJ and HR collectively [93]. Recent work showed that exposure to hyperthermia can restrict the activity of DNA-PKs in addition to reducing protein levels of KU70, KU80, BRCA1 and 53BP1 with the first two in greater extent [94]. Finally, given that various chemotherapeutic agents have the ability to trigger the induction of DSBs, inhibitors of DNA ligases and/or DNA-PKs appear to sensitize tumor cells to chemotherapeutic drugs thus providing alternative therapeutic strategies which potentially can be more effective [95,96].…”
Section: Non-homologous End Joining (Nhej)mentioning
confidence: 99%
“…However, the spectrum of different lesions induced by a single DNA damaging agent, as well as the possibility that hyperthermia targets multiple DNA repair pathways, prevents conclusive interpretation of data obtained using this genetic approach. Indeed, multiple DNA repair pathways, such as base excision repair [66] for single strand DNA lesions and non-homologous end joining for double strand breaks [100], are believed to be inhibited by hyperthermia [96]. However, the results obtained in these studies are often based on experiments done with temperatures above 43 C, so it remains unclear whether inhibition of these DNA repair pathways add to the effects of mild hyperthermia.…”
Section: Hyperthermia and Dna Repairmentioning
confidence: 68%
“…Several lines of evidence show that factors involved in DSB repair are likely to be affected by heat shock, for example, Ku heterodimer (Ku70/Ku80) [33][34][35][36], MRN complex [37][38][39], breast cancer susceptibility gene 1 (BRCA1) [40], BRCA2 [41] and RAD51 [41,42]. Heat shock affects these proteins by causing denaturation, cytoplasmic translocation from the nucleus, and protein degradation by the proteasome pathway [43].…”
Section: Discussionmentioning
confidence: 99%